Interview with Bruce G. Carruthers. Brexit, Bitcoin, Big Data: How Historical Analysis Helps Shed Light on What the Future Holds - CarruthersBruce G. (Journal of Economic Sociology, 2019)
During the first part of the conversation, Bruce Carruthers reflects upon the structural differences between European and North American academic settings and between sociological departments and business schools, considering graduate training and further ascending up the career ladder. He elaborates on his current research, a historical study of credit and credit decision-making in the United States in the nineteenth and twentieth centuries, but he also works on corporate social responsibility and taxation and the adoption of “business like” characteristics by US museums. Carruthers points out that working at a bunch of intersections between different branches of sociology allows him to be intellectually inclusive in his work. He shares his personal recipe for economic sociology. According to him, a good economic sociologist has to be curious about the economy and willing to do additional work and go beyond his or her sociological training to become knowledgeable in economic phenomena. Taking advantage of communication with colleagues from other fields of knowledge may also contribute to a good practice of conducting an economic sociological study. Speculating about the future of credit relations, Carruthers suggests that dystopian sci-fi TV shows pose some relevant issues to credit scoring. The combination of how widely the information can circulate and what the individual scores are based on provoke governmentality fears about ratings and rankings. As he puts it, the developing Chinese social credit system, which involves almost no privacy in relation to the State, may be nerve-racking if it gets full expression—quite the opposite future Carruthers predicts for the peer-to-peer platforms that promised to challenge the financial market. Once the promotional hype is over, as he points out, big financial institutions will likely take over the successful platforms, and tech platforms could do the business of intermediation may pop up. With respect to promising topics in sociology, Carruthers recommends directing our attention toward the incorporation of big data into research and the expansion of big data analysis skills, as the future of economic sociological research lies therein.